Preparation, characterization and in ovo vaccination of dextran-spermine nanopeprints dna vaccine coexpressing the fusion and hemagglutinin genes against newcastle disease - Firouzamandi, Masoumeh; Moeini, Hassan; Hosseini, Seyed Davood; Bejo, Mohd Hair; Omar, Abdul Rahman; Mehrbod, Parvaneh; El Zowalaty, Mohamed Ezzat; Webster, Thomas Jay; Ideris, Aini (Dove Medical Press, 2016)
Plasmid DNA (pDNA)-based vaccines have emerged as effective subunit vaccines against viral and bacterial pathogens. In this study, a DNA vaccine, namely plasmid internal ribosome entry site-HN/F, was applied in ovo against Newcastle disease (ND). Vaccination was carried out using the DNA vaccine alone or as a mixture of the pDNA and dextran-spermine (D-SPM), a nanoparticle used for pDNA delivery. The results showed that in ovo vaccination with 40 µg pDNA/egg alone induced high levels of antibody titer (P<0.05) in specific pathogen-free (SPF) chickens at 3 and 4 weeks postvaccination compared to 2 weeks postvaccination. Hemagglutination inhibition (HI) titer was not significantly different between groups injected with 40 µg pDNA + 64 µg D-SPM and 40 µg pDNA at 4 weeks postvaccination (P>0.05). Higher antibody titer was observed in the group immunized with 40 µg pDNA/egg at 4 weeks postvaccination. The findings also showed that vaccination with 40 µg pDNA/egg alone was able to confer protection against Newcastle disease virus strain NDIBS002 in two out of seven SPF chickens. Although the chickens produced antibody titers 3 weeks after in ovo vaccination, it was not sufficient to provide complete protection to the chickens from lethal viral challenge. In addition, vaccination with pDNA/D-SPM complex did not induce high antibody titer when compared with naked pDNA. Therefore, it was concluded that DNA vaccination with plasmid internal ribosome entry site-HN/F can be suitable for in ovo application against ND, whereas D-SPM is not recommended for in ovo gene delivery.